DIKSI DAN MAKNA DALAM KOMUNIKASI: PILAR KONSEPTUAL DALAM PERKEMBANGAN MASYARAKAT DIGITAL KONTEMPORER - Parulian Sibuea; Rahayu Manila Guci; Ananda Ivan Adrian Hsb (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to examine the role of diction in shaping the meaning of communication and its contribution to social dynamics in the context of contemporary digital society. Using a qualitative approach, the research analyzes how word choice (diction) influences message clarity, establishes emotional connections between communicators and audiences, and creates context-relevant meanings in both formal and informal communication. The findings indicate that accurate diction significantly determines communication success and helps prevent ambiguity, misunderstanding, and interpretative conflict. In a digital landscape characterized by cultural diversity and rapid information flow, diction also functions as a tool for discourse construction and social symbolism that shapes public opinion. This study emphasizes the importance of linguistic awareness and cultural sensitivity in word selection to ensure inclusive, ethical, and meaningful communication. These findings offer practical implications for developing communication competence in the digital era and highlight diction as a crucial conceptual pillar in the ongoing process of social transformation.